2020
DOI: 10.1093/aob/mcaa171
|View full text |Cite
|
Sign up to set email alerts
|

Rice withSUB1QTL possesses greater initial leaf gas film thickness leading to delayed perception of submergence stress

Abstract: Background and Aims Submergence tolerance in rice is primarily attributed to SUB1 gene action, but other associated traits such as leaf gas film (LGF) thickness, leaf hydrophobicity, porosity and leaf density have been known to aid submergence tolerance in rice. However, association of these traits with SUB1 QTL is not well worked out. In this study, we aim to investigate (i) whether the presence of SUB1 QTL in the genetic background has any influence on the thickness of the leaf gas film, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The primary function of SUB1A in submergence tolerance is to reduce energy reserve metabolism by limiting ethylene synthesis and responsiveness, suppressing gibberellic acid (GA) responsiveness, and activating brassinosteroid synthesis, thereby restricting shoot elongation and avoiding energy starvation under stress (Barding et al, 2012(Barding et al, , 2013Fukao et al, 2006;Fukao and Bailey-Serres, 2008;Schmitz et al, 2013). In addition to metabolic adjustments, SUB1A increases the thickness of the leaf gas film under submergence, enhancing the surface hydrophobicity of leaves (Chakraborty et al, 2021). Moreover, it has been shown that SUB1A is phosphorylated by mitogen-activated protein kinase 3 (MPK3), and that the presence and activity of MPK3 are correlated with submergence tolerance in rice plants containing SUB1A (Singh and Sinha, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The primary function of SUB1A in submergence tolerance is to reduce energy reserve metabolism by limiting ethylene synthesis and responsiveness, suppressing gibberellic acid (GA) responsiveness, and activating brassinosteroid synthesis, thereby restricting shoot elongation and avoiding energy starvation under stress (Barding et al, 2012(Barding et al, , 2013Fukao et al, 2006;Fukao and Bailey-Serres, 2008;Schmitz et al, 2013). In addition to metabolic adjustments, SUB1A increases the thickness of the leaf gas film under submergence, enhancing the surface hydrophobicity of leaves (Chakraborty et al, 2021). Moreover, it has been shown that SUB1A is phosphorylated by mitogen-activated protein kinase 3 (MPK3), and that the presence and activity of MPK3 are correlated with submergence tolerance in rice plants containing SUB1A (Singh and Sinha, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rice genotypes tolerant to flooding stress at the germination stage can withstand the stress through overexpression of amylolytic and fermentative enzymes, greater ethylene production, and increased coleoptile growth (Vijayan et al 2018). Whereas rice genotypes capable to tolerate complete submergence restrict ethylene production vis-a-vis gibberellins biosynthesis, and limit the use of non-structural carbohydrates through suppressing amylolytic enzyme activity (Chakraborty et al 2021a). Therefore, QTLs/genes for stagnant flooding tolerance could be different from that of submergence or deep-water stresses.…”
Section: Discussionmentioning
confidence: 99%
“…An important QTL associated with submergence tolerance is SUB1 (submergence 1) (Xu et al, 2006;Fukao and Bailey-Serres, 2008). A recent study affirmed that SUB1 influences concomitant leaf gas film thickness and surface hydrophobicity (Chakraborty et al, 2021). Leaf gas film provides improved ethylene dissipation and decreased in-planta accumulation.…”
Section: Abiotic Stressmentioning
confidence: 99%
“…Leaf gas film provides improved ethylene dissipation and decreased in-planta accumulation. This eventually results in the delay of ethyleneinduced leaf senescence upon submergence stress (Chakraborty et al, 2021). Another flooding stress-related condition involves the exposure of plants to hypoxia.…”
Section: Abiotic Stressmentioning
confidence: 99%